Determinants of Menstrual Hygiene Management Practices Among Adolescents: A Cross-Sectional Study - Susanti, Henny Dwi; Marta, Mirna Dian; Kholidah, Nurilla; Anggraeni, ika Rizki; Moravcová, Markéta; Chung, Min-Huey (Nurse Media Journal of Nursing, 2025)
Background: Menstrual hygiene management (MHM) is critical for adolescents’ health and well-being; however, challenges such as limited water, sanitation, and hygiene (WASH) facilities, stigma, and lack of education persist in low- and middle-income countries. In Indonesia, most studies have focused on knowledge and attitudes rather than the determinants of practices, leaving this area underexplored.Purpose: This study aimed to identify the determinants of menstrual hygiene management practices among adolescents.Methods: This cross-sectional study was conducted online with 365 females aged 12 to 24 years using purposive sampling. Data collection tools included the Menstrual Hygiene Management (MHM) questionnaire, the Depression Anxiety Stress Scale (DASS-21), the Multidimensional Scale of Perceived Social Support (MSPSS), and demographic questionnaires. Associations were analyzed using independent t-test, Pearson correlation, and linear regression.Results: Bivariate analysis showed that higher MHM scores were significantly associated with older age, older age at menarche, higher education level, longer menstrual cycles, employment, higher family income, and urban residence. In contrast, a history of dysmenorrhea was negatively associated with MHM scores. Linear regression analysis revealed that menstrual cycle length was a significant positive predictor of MHM, while a history of dysmenorrhea was a significant negative predictor.Conclusion: Menstrual hygiene management was generally good among adolescents. Significant determinants included menstrual cycle length and history of dysmenorrhea. These findings underscore the importance of addressing biological and physiological factors in menstrual health education. Public health programs should integrate menstrual cycle education and dysmenorrhea management strategies to improve hygiene practices.